المعالجة الإعلامية للقضايا التربية والتعليم - سيليني, غنية (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2020)
تهدف الدراسة إلى التعرف على طبيعة المعالجة الإعلامية لقضايا إضراب المعلمين من خلال مقالات جريدة الشروق الواقعة في الموسم الدراسي 2019-2020، حيث تم إجراء الدراسة على عينة من أعداد من المقالات الإلكترونية وذلك باستخدام تحليل المضمون، وقد قمنا بتقسيم الفئات إلى فئة المصدر، الاتجاه، الأنواع الصحفية، اللغة المستخدمة، والمعالجة الفنية، فئة الموضوع، الشخصيات الفاعلة، الأهداف، والجمهور المستهدف. وتوصلت الدراسة إلى نتائج: - احتل موضوع قضايا التربية والتعليم وبالأخص إضراب أساتذة التعليم الابتدائي أهمية في أجندة وأولويات الشروق الإعلامية نظرا للتغطية والمتابعة المكثفة للموضوع، وتناولته من جميع جوانبه بكل جزئياته. - الأنواع الإخبارية هي أكثر الأنواع الصحفية المستخدمة والمعتمدة في نشرة الحصاد للتناول الإعلامي لقضايا الإرهاب، وذلك من أجل إطلاع المشاهد بكافة مستجدات والأخبار المتعلقة بالحدث خاصة ذوي الجنسية الجزائرية، كما اعتمدت الحوار لطرح وجهات نظر أخرى حول القضية. - وفرت الجريدة تغطيات ميدانية في مختلف مناطق الوطن لسهولة الوصول إلى مصادر الخبر، مع تواجد مراسلين صحفيين عبر مختلف مناطق البلاد. - حاولت الشروق قدر المتاح أن تقوم بدورها الإعلامي والإخباري والتوعوي بكل موضوعية ونزاهة وصدق، من خلال نقل الحقائق وإسنادها إلى مصادر موثوقة ورسمية ومعروفة بطبيعة المعلومات التي تداولها، وأظهرت تعاطفا مع المعلمين غطى على بعض السقطات الإعلامية المضادة لمواقف المعلمين وقضاياهم The study aims to identify the nature of media treatment of teachers' strike issues through the articles of Echorouk paper located in the 2019-2020 academic season، where the study was conducted on a sample of numbers of electronic articles using content analysis، and we divided the categories into the source category، direction، Journalistic genres، language used، technical processing، topic category، actors، goals، and target audience. The study reached results: - The issue of education issues، in particular the primary education teachers ’strike، occupied an importance in the media agenda and priorities of Echorouk due to the extensive coverage and follow-up of the issue، and it covered it in all its aspects with all its parts. - News types are the most used and approved press types in the Harvest Bulletin for media coverage of terrorism issues، in order to inform the viewer of all developments and news related to the event، especially those of Algerian nationality. The dialogue was also adopted to provide other views on the issue. - The newspaper provided field coverage in various regions of the country for easy access to news sources، with reporters present throughout the various regions of the country. - Echorouk tried as much as possible to fulfill its informational، informational and educational role in all objectivity، integrity and sincerity، by transferring the facts and assigning them to reliable and official sources known to the nature of the information that was circulated، and showed sympathy with the teachers، which covered some media hiccups against the attitudes of teachers and their issues